Melatonin Reduces Oxidative Stress in the Right Ventricle of Newborn Sheep Gestated under Chronic Hypoxia - Alejandro Gonzaléz-Candia; Pamela V. Arias; Simón A. Aguilar; Esteban G. Figueroa; Roberto V. Reyes; Germán Ebensperger; Aníbal J. Llanos; Emilio A. Herrera (MDPI AG, 2021)
Pulmonary arterial hypertension of newborns (PAHN) constitutes a critical condition involving both severe cardiac remodeling and right ventricle dysfunction. One main cause of this condition is perinatal hypoxia and oxidative stress. Thus, it is a public health concern for populations living above 2500 m and in cases of intrauterine chronic hypoxia in lowlands. Still, pulmonary and cardiac impairments in PAHN lack effective treatments. Previously we have shown the beneficial effects of neonatal melatonin treatment on pulmonary circulation. However, the cardiac effects of this treatment are unknown. In this study, we assessed whether melatonin improves cardiac function and modulates right ventricle (RV) oxidative stress. Ten lambs were gestated, born, and raised at 3600 m. Lambs were divided in two groups. One received daily vehicle as control, and another received daily melatonin (1 mg·kg−1·d−1) for 21 days. Daily cardiovascular measurements were recorded and, at 29 days old, cardiac tissue was collected. Melatonin decreased pulmonary arterial pressure at the end of the experimental period. In addition, melatonin enhanced manganese superoxide dismutase and catalase (CAT) expression, while increasing CAT activity in RV. This was associated with a decrease in superoxide anion generation at the mitochondria and NADPH oxidases in RV. Finally, these effects were associated with a marked decrease of oxidative stress markers in RV. These findings support the cardioprotective effects of an oral administration of melatonin in newborns that suffer from developmental chronic hypoxia.